Performance Evaluation of Water Delivery System for Command Area of Amarpura Minor of Som-Kagdar Irrigation Project, Rajasthan - Singh, Sangram; Kothari, Mahesh; Purohit, R C (Journal of Agricultural Engineering, 2006)
This study examines water delivery performance of the Amarpura minor, which is located on left main canal of Som-kagdar irrigation project. Outlets wise performance was evaluated, using the adequacy, equity, dependability and relative water supply indicators. These indicators were calculated for the fifteen outlets for the 5-month irrigation period of Rabi season (2004-05), using measured water deliveries and calculated crop water requirements. Digital current meter was used to measure the outlet discharge during the season. Crop water requirements were calculated using CROPWAT. The outlet wise water delivery performance indicators have shown poor performance of the system. Considering the irrigation season and the system as a whole, the calculated indicator’s average values were found as "poor" for adequacy, equity and dependability. These results have also shown that there is a systemic water delivery problem. The analysis of results of the spatial and temporal dimensions of these indicators has show that factors causing this problem are derived partly due to physical state of system and partly due to improper operation and management.